A NOTE ON NORMALISED HEAT DIFFUSION FOR GRAPHS. Issue 1 (23rd August 2020) - NICA, BOGDAN
Abstract : We show that, on graphs which have precisely three distinct Laplacian eigenvalues, heat diffusion enjoys a monotonic behaviour.